PENGARUH METODE BERCERITA TERHADAP KEMAMPUAN MENYIMAK BERDASARKAN GENDER TK ISLAM BINA 45 PONTIANAK TIMUR - Wihdah, Mukhlisah El; R, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to determine the effect of using storytelling method towards listening ability based on gender in children aged 5-6 years in Bina 45 Islamic Kindergarten, East Pontianak. The method used in this study was an experiment with a quantitative approach. This study was conducted through a Pre-Experimental Research Design in the form of ?One Group Pre-test Post-test design?. The sample in this study was group B4 with 23 children as the experimental group. Direct observation and documentation techniques were used for the data collection, as well as associative and statistical analysis were applied in data analysis by referring to the t-test result. According to the data analysis, by denoting the average differences between listening ability level of male children with the value of 29,23 (pre-test) and 89,62 (post-test) and the female children with the value of 36 (pre-test) and 90 (post-test), and the influence of the storytelling method towards children?s listening ability based on gender, it revealed tcount of the male children with the value of 5,605 as well as ttable with 5% of significant level for two-party test dk=24, therefore, obtained the value of 2,064. As well as on the other gender, tcount of the female children was 2,852 with the 5% of significant level for two-party test dk=18, therefore, the value of 2,101 was obtained. Based on the calculation, it was found that tcount>ttable hence, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It concluded that the use of storytelling method was significant towards listening ability based on gender on children aged 5-6 years old in Bina 45 Islamic Kindergarten, East Pontianak. Keywords: Storytelling Method, Listening, Gender